1998
DOI: 10.1123/ssj.15.3.263
|View full text |Cite
|
Sign up to set email alerts
|

The Role Exit of Professional Athletes

Abstract: Previous research on the role transition of ex-athletes to a new career is somewhat limited because the studies have applied theories that do not fit the unique characteristics of athletes. This research uses another approach, Ebaugh’s role exit theory to understand the role exit process of professional athletes. Ebaugh claims that her theory, is applicable to all role exits. We found that Ebaugh’s theory applies to athletes, but with modification. Data were collected from interviews with 27 former professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0
16

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 12 publications
0
44
0
16
Order By: Relevance
“…This is a significant finding due to the urgency and necessity of developing a career-minded focus in student athletes. Drahota & Eitzen (1998) found that for those athletes who had not planned for their futures, exiting involuntarily heightened the difficulty of their transition into a new role. Student athletes that have a career minded focus will have better chances to succeed in their transitions and future non-athletic careers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a significant finding due to the urgency and necessity of developing a career-minded focus in student athletes. Drahota & Eitzen (1998) found that for those athletes who had not planned for their futures, exiting involuntarily heightened the difficulty of their transition into a new role. Student athletes that have a career minded focus will have better chances to succeed in their transitions and future non-athletic careers.…”
Section: Discussionmentioning
confidence: 99%
“…The scarcity of qualitative studies (Parker, 1994;Drahota & Eitzen, 1998), and less attention to research designs that utilise both quantitative and qualitative methods motivated this investigation. This approach, which utilises an open-ended narrative response, is unique to the career transition literature of sport and non-sport participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blau's (1973) research emphasised the process of (re)socialization between roles. The alteration of role expectations and associated gains and losses of status (role identity) as the result of role exit (see also Drahota and Eitzen, 1998). Bringing these points together, an accepted definition of role exit is defined as the "departure from any role that is central to one's self-identity" (Ebaugh, 1988: 149).…”
Section: Role Exit and Sport Event Volunteeringmentioning
confidence: 99%
“…Hochschild, 1975;Carter and Cook, 1995;Achenbaum and Bengtson, 1994;Curtis and Ennis, 1998). Inherent to the concept of role exit and related theories such as the theory is the process of transition (Drahota and Eitzen, 1998;Guillemard and Rein, 1993) or the passing from adulthood to pensioner. In the case of the World Firefighters Games 2008 (WFG'08), transition occurred in the form of the individual moving from WFG'08 volunteer to ex-WFG'08 volunteer.…”
Section: Role Exit and Sport Event Volunteeringmentioning
confidence: 99%